Flow dynamics and scalar transport in drinking water contact tanks - Barnett, Taylor C., author; Venayagamoorthy, Subhas Karan, advisor; Julien, Pierre Y., committee member; Sakurai, Hiroshi, committee member (Colorado State University. Libraries, 2013)
The research and studies presented in this thesis focus on ways to improve the internal hydraulics of chlorine contact tanks used in drinking water disinfection systems. This was accomplished through the use of computational fluid dynamics (CFD) and physical tracer studies of a number of different systems. Three primary tank modifications were investigated in these studies: internal baffling; inlet modifications; and random packing material. The findings from these studies were then applied in a case study of the Jamestown chlorine contact tank. All of the studies presented in this thesis use the baffle factor (BF) designation as defined by the United States Environmental Protection Agency as the primary indicator of a system's disinfection efficiency. The CFD models used for the internal baffling study were first validated using a laboratory scale study of the Embsay chlorine contact tank in Yorkshire, England. This tank footprint was then modified to replicate a precast concrete tank that was installed in the Hydraulics Laboratory located at the Engineering Research Center (ERC) at Colorado State University. This concrete tank was used as the footprint for a parametric study in which the number and length of internal baffles were modeled in various configurations. The internal hydraulics of this baffle tank were optimized using only two dimensionless relationships namely: the baffle opening ratio L* and the baffle opening to channel width ratio Lbo/Wch. The resulting tank geometry from these two relationships yielded a BF of 0.80 and also maximized the length to width ratio of each channel within the concrete tank. The inlet modification study was performed to investigate how the BF of a 400-gallon doorway storage tank could be improved. Three different inlet types with two inlet sizes were modeled and simulated for six different flow rates. Three of these CFD simulations were then physically tested using both saline and lithium tracers to validate the computer models. Key findings from this study show that the size of the inlet and its orientation play a dominant role in the internal hydraulics of the system. For the random packing material study, three different packing material sizes, two tank sizes, and two different flow rates were tested. CFD models were not feasible due to the randomness of how the packing material would settle in these contact tanks. Over 64 saline tracer studies and 6 lithium tracer studies were conducted to complete this study. Key findings show that the initial BF of the system and the volume of the tank filled with the packing material were the dominant variables in the study. The tank size, flow rate, and packing material size had little to no impact on the performance. The Jamestown case study presented in this thesis used findings from both the internal baffle study and the inlet modification study. The BF of the contact tank would fluctuate annually between 0.52 and 0.63 due to a shift in flow regimes caused by a change in the system's flow rate. This turbulent to laminar flow regime change was validated with the use of CFD models coupled with physical tracer studies. Several inlet modifications were investigated using CFD to determine what modifications, if any, the plant operators should implement. Key findings from the CFD models showed that with the proper inlet modification, the BF of the system could be stabilized at 0.63 during both the high flow summer months and low flow winter months.
Keywords: baffle; CFD; computational fluid dynamics; contact tank; packing material; water treatment